Predicting incident radiographic knee osteoarthritis in middle‐aged women within four years: the importance of knee‐level prognostic factors - Garriga, C; Sánchez‐Santos, MT; Judge, A; Hart, D; Spector, T; Cooper, C; Arden, NK (Wiley, 2019)
Objective To develop and internally validate risk models and a clinical risk score tool to predict incident radiographic knee osteoarthritis (RKOA) in middle‐aged women.